2020
DOI: 10.1177/0363546519897033
|View full text |Cite
|
Sign up to set email alerts
|

Delaminated Rotator Cuff Tears Showed Lower Short-term Retear Rates After Arthroscopic Double-Layer Repair Versus Bursal Layer–Only Repair: A Randomized Controlled Trial

Abstract: Background: The rotator cuff is known to consist of 2 macroscopically visible layers that have different biomechanical properties. Sometimes the inferior layer may be neglected during rotator cuff repair. However, it is controversial whether double-layer (DL) repair is superior to single-layer (SL) repair in terms of retear rate and outcome. Purpose: To investigate whether DL as compared with SL repair could decrease retear rates after arthroscopic reconstruction of posterosuperior rotator cuff tears. Study De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Several reports since 2005 agreed that the presence of delaminated tears is a negative prognostic factor in functional and morphologic results after the repair of rotator cuff tendons [ 14 , 15 , 16 , 29 , 32 , 35 , 36 ]. An improvement in biomechanical properties, improved clinical outcomes, and decreased retear rates have been reported for the repair of delaminated tears [ 31 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. The intratendinous laminated component of rotator cuff tears should be repaired using a number of surgical techniques to restore normal biomechanics of the cuff and reduce the risk of repair failures [ 10 ].…”
Section: Treatment and Clinical Outcomementioning
confidence: 99%
“…Several reports since 2005 agreed that the presence of delaminated tears is a negative prognostic factor in functional and morphologic results after the repair of rotator cuff tendons [ 14 , 15 , 16 , 29 , 32 , 35 , 36 ]. An improvement in biomechanical properties, improved clinical outcomes, and decreased retear rates have been reported for the repair of delaminated tears [ 31 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. The intratendinous laminated component of rotator cuff tears should be repaired using a number of surgical techniques to restore normal biomechanics of the cuff and reduce the risk of repair failures [ 10 ].…”
Section: Treatment and Clinical Outcomementioning
confidence: 99%
“…Mochizuki et al reported that the super cial and deep layers should be individually sutured because the footprints of the 2 layers are anatomically different [11,14]. Some studies have described the usefulness of DLSB, comparing with EMSB and the bursal layer-only repair suture bridge (BLSB) [6,8,35,36]. This is based on the merit of DLSB in repairing the super cial and deep layers to an anatomically appropriate footprint [35].…”
Section: Discussionmentioning
confidence: 99%
“…The delamination of the rotator cuff has been described as a horizontal lesion between the super cial and deep layers [1,2]. Delamination is observed in 36-82% of rotator cuff tear cases [3][4][5][6][7][8][9] and its presence is considered a risk factor for postoperative retear after rotator cuff repair [4]. Double-row double layer xation was reported as a repair method of the stump of delaminated rotator cuff tears, but a high incidence of retear in large and massive rotator cuff tear cases has been known [2,10], and optimal xation method for rotator cuff stump with delamination has yet been under debate.…”
Section: Introductionmentioning
confidence: 99%
“…Although diagnostic methods and surgical techniques have developed significantly over the last decade, non-healing and retear rates of surgically repaired tendons are still unacceptably high [ 6 , 15 , 16 , 35 , 37 ]. This has led to a growing interest in aetiology of tendon tearing and biology of healing.…”
Section: Introductionmentioning
confidence: 99%